Heart Rate Detection of Stress Levels for Pregnant Women - Yuli Wahyuni; Muhammad Abdulrohman Pany (Universitas Djuanda, 2022)
During pregnancy, there are changes because the fetus begins to grow and develop in the pregnant woman's stomach. Physiology greatly influences its development, especially in hormonal and metabolic changes that affect the psychological stress level of pregnant women. This study aims to determine the initial action to detect heart rate by looking at stress levels in pregnant women. The results of stress measurements are not normal when the heart rate is less than 60 bpm and more than 100 bpm, while in conditions of more than 60 bpm and less than 100 bpm, the results obtained are normal conditions. This study uses a hardware programming approach with the stages: Project Planning, Research, Component Testing, Mechanical System Design, Functional Test, Functional Test, Overall System Functional Test, System Optimization. The results show that this tool has worked well in monitoring heart rate when stressed in real-time using a pulse sensor displayed via telegram notifications in the form of total data. Still, because it is only in the form of notifications, there is no storage in the form of a database.